An exploration of postgraduate students’ conceptions of the nature of argument - Hallam, Susan; Francis, Hazel (Psychology: the Journal of the Hellenic Psychological Society, 2020)
Study at postgraduate level requires the development of the skills of argument in developing both theoretical and empirical work. This study aimed to explore conceptions of argument among post-graduate students using qualitative methods within a quasi-experimental design. Thirty nine students, divided into two groups, participated. Each group completed two tasks in a different order. Task 1 required each student to describe in writing how an argument might be used to add to knowledge and to list any characteristic structural features of an argument. Task 2 required the reading of a short text which was then evaluated in relation to its use of argument. For each task, small group discussion of differences, similarities and changes in views was tape-recorded. The findings showed considerable agreement regarding the main characteristics of an argument but variability in how argument was perceived to add to knowledge. The findings are discussed in relation to the work of Kuhn (1991) and in terms of their educational implications.